Geotechnical Modelling. - Muir Wood, David (Milton : Taylor & Francis Group, 2004)
This book enables practising engineers to make informed decisions concerning soil model boundary conditions and the choice of elements in Finite Element models. Ideal for MSc and MEng students and for use on CPD courses.
6.6 Pore fluid -- 6.7 Site investigation -- 6.8 Instrumentation -- 6.9 Modelling and testing -- 6.10 Closure -- 7 Theoretical modelling -- 7.1 Introduction -- 7.2 Elastic stress distributions -- 7.3 Plastic failure analysis -- 7.3.1 Bound theorems -- 7.3.2 Structural example -- 7.3.3 Continuum problems-Mohr's circle -- 7.3.4 Bearing capacity of cohesive soil -- 7.3.5 Wall retaining cohesive soil -- 7.3.6 Bearing capacity of frictional soil -- 7.4 One-dimensional consolidation -- 7.4.1 Parabolic isochrones -- 7.4.2 General power law approximate solution -- 7.4.3 Pore pressures for stability analysis of embankment on soft clay -- 7.5 Macroelement models -- 7.5.1 Box model -- 7.5.2 Wall model -- 7.5.3 Footing model -- 7.5.4 Extended Newmark sliding block model -- 7.6 Closure -- 8 Soil-structure interaction -- 8.1 Introduction -- 8.2 Elastic analyses -- 8.2.1 Beam on elastic foundation -- 8.2.2 Pile under lateral loading -- 8.2.3 Pile under axial loading -- 8.2.4 Piled raft -- 8.3 Serviceability calculations -- 8.4 Relative foundation stiffness -- 8.5 Downdrag on pile -- 8.6 Settlement reducing piles -- 8.7 Flexible retaining wall -- 8.8 Tunnel lining -- 8.9 Pile in displacing ground -- 8.10 Integral bridge abutment -- 8.11 Closure -- 9 Envoi -- Bibliography -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Models; Electronic books